2017
DOI: 10.1038/s41598-017-02698-w
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between the expression of genes involved in drug metabolism and the blood level of tacrolimus in liver transplant receipts

Abstract: Immunosuppressive medications, such as tacrolimus and mycophenolate mofetil, are commonly used for reducing the risk of organ rejection in receipts of allogeneic organ transplant. The optimal dosages of these drugs are required for preventing rejection and avoiding toxicity to receipts. This study aimed to identify the correlation between the expression profiling of genes involved in drug metabolism and the blood level of tacrolimus in liver transplant receipts. Sixty-four liver transplant receipts were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Among all the covariates we studied, pre-operation serum creatinine concentration of recipients in the CP was the only variable that showed statistical significance. In keeping with our findings, serum creatinine was previously shown to be relevant in tacrolimus metabolism (Wang et al, 2017), whereas the other baseline characteristics we studied have been reported to have no effect. Interestingly, serum creatinine only influenced tacrolimus metabolism during CP, showing that, to a certain extent, the major factors affecting tacrolimus metabolism were genetic.…”
Section: Discussionsupporting
confidence: 90%
“…Among all the covariates we studied, pre-operation serum creatinine concentration of recipients in the CP was the only variable that showed statistical significance. In keeping with our findings, serum creatinine was previously shown to be relevant in tacrolimus metabolism (Wang et al, 2017), whereas the other baseline characteristics we studied have been reported to have no effect. Interestingly, serum creatinine only influenced tacrolimus metabolism during CP, showing that, to a certain extent, the major factors affecting tacrolimus metabolism were genetic.…”
Section: Discussionsupporting
confidence: 90%
“…However, CYP4F2 metabolizes the ester prodrug of gemcitabine and the antiparasitic pafuramidine [57]. In addition, CYP4A11 exhibited metabolism of the immune suppressant tacrolimus to an inactive form [58]. Although the turnover rates were low compared to those of CYP3A4, CYP4F11 exhibited catalytic activity towards commonly used drugs such as erythromycin, benzphetamine, and chlorpromazine [36,37,59].…”
Section: Role Of the Cyp4 Family In The Metabolism Of Drugsmentioning
confidence: 99%
“…CYP450 is an essential metabolic enzyme present in most organisms, of which the highest levels are found in the endoplasmic reticulum of liver cells, which helps in the biotransformation of most exogenous substances . Studies have found that CYP450 could catalyze AA to 20-HETE and EETS for lipid metabolism, inflammatory reaction, and oxidative stress. As the metabolites catalyzed by COXs from AA, PGs are the key regulators of the renal vasomotor tone. Therefore, abnormal generation of PGs could cause anoxia and reduced renal blood flow, which may stimulate renal injury, inflammation, and fibrotic injury.…”
Section: Discussionmentioning
confidence: 99%